2006
DOI: 10.1007/11677482_3
|View full text |Cite
|
Sign up to set email alerts
|

The AMI Meeting Corpus: A Pre-announcement

Abstract: The AMI Meeting Corpus is a multi-modal data set consisting of 100 hours of meeting recordings. It is being created in the context of a project that is developing meeting browsing technology and will eventually be released publicly. Some of the meetings it contains are naturally occurring, and some are elicited, particularly using a scenario in which the participants play different roles in a design team, taking a design project from kick-off to completion over the course of a day. The corpus is being recorded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
466
0
4

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 642 publications
(502 citation statements)
references
References 5 publications
(4 reference statements)
0
466
0
4
Order By: Relevance
“…C2 contains all talk-shows (27 in total) broadcasted by Radio Suisse Romande during February 2005. C3 is the AMI meeting corpus [6], a collection of 138 meeting recordings involving 4 persons each and with an average length of 19 minutes and 50 seconds. The roles of C1 and C2 share the same names and correspond to similar functions: the Anchorman (AM), the Second Anchorman (SA), the Guest (GT), the Interview Participant (IP), the Headline Reader (HR), and the Weather Man (WM).…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…C2 contains all talk-shows (27 in total) broadcasted by Radio Suisse Romande during February 2005. C3 is the AMI meeting corpus [6], a collection of 138 meeting recordings involving 4 persons each and with an average length of 19 minutes and 50 seconds. The roles of C1 and C2 share the same names and correspond to similar functions: the Anchorman (AM), the Second Anchorman (SA), the Guest (GT), the Interview Participant (IP), the Headline Reader (HR), and the Weather Man (WM).…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…For these experiments, we use the AMI meetings corpus [1]. The corpus consists of about 100 hours of recorded and annotated meetings, divided into scenario and nonscenario meetings.…”
Section: Corporamentioning
confidence: 99%
“…Apart from "AV 16.3", we have also explored the suitability of several other publicly available audio-visual datasets, such as "CLEAR" [55], "AMI" [56] and "SPEVI" [57], and concluded that only the AV 16.3 dataset is suitable for the evaluation of our proposed methods. It complies with our requirements in terms of having circular microphone arrays with calibration information, mostly talking speakers, and challenging scenarios such as occlusion and rapid movements of the speakers.…”
Section: A Setupmentioning
confidence: 99%